The Comparative Analysis of Urban Employment Indexes in Iran Towns - A. Zangiabadi; A. Rahimi; S. Mosayebi (جغرافیا و برنامه‌ریزی محیطی, 2013)
Extended abstract1- IntroductionThe role of employment in the vitality of modern urban societies’ life is not a mystery to anyone. Unemployment and the ensuing issues constitute the most complicated of current urban planning issues which give birth to a plethora of deleterious social, cultural, security and even environmental complexities as well as to some certain economic consequences which directly or indirectly influence all aspects of urban planning in a sense that one could say many of the problems and issues of urban societies result from ill employment structures. Since employment and inequality are two interrelated and interdependent issues, unequal employment opportunities in different areas paves the way for inequality in other domains of development and results in developmental inequality among different areas, an inequity in creating employment opportunities, thus making some areas more developed than others which in long run leads to a lack of equilibrium in urban system of the country. Therefore, comparing and analyzing urban employment indices of different areas of the country and categorizing them in terms of urban employment development and providing a logical prioritization can prepare the ground for a well-informed intervention in urban employment planning of the country along with maintaining the community system equilibrium and establishing stable urban development. 2- MethodologyIn this study, Iranian cities are examined and compared in terms of urban employment indices using Maurice model and TOPSIS algorithm and arranged in the order of their urban development level and categorized, and the results were displayed in GIS environment on the map using ArcMap software. SPSS was employed to analyze and the data and test the hypotheses. The data used in indexing were the results of the public census of 1385 (2006) retrieved from the portal of the national statistical center of Iran.3- DiscussionThe cities were divided into 4 homogenous categories based on their employment development which accordingly, from a total of 336 cities, 19 cities are placed in level one, 123 in level 2. 146 in level 3 and 87 cities are placed in the last level. Three cities of Roshtkhar, Sarayan and Mahvelat have the three top places in terms of employment development, against Koohrang, Abu Musa, and Masjed Suleiman standing in the last places in that respect. The value (the cities’ level of development) fluctuates between the upper limit of 0.556 and the lower limit of 0.286 and difference between its highest and lowest values is 0.270 and the first city (Roshtkhar) has developed 1.943 times more than the last city (Koohrang). The mean of urban development in the cities is 0.397. The level of inequality in terms of urban development among Iranian cities is low (about 0.1). There is a slight inverse correlation (-0.217) between the two parameters of “spatial share of urban population of the cities” and their “urban employment development.” According to the mean of urban employment development of the cities of each province, the provinces were divided into homogenous groups in a manner that 4 provinces were placed in level one, 13 provinces in level two, 8 provinces in level three and 5 provinces in the last level (four) of development the major concentration being among the middle categories. In this regard, the provinces of Central Khorasan, Northern Khorasan, and Kohkiluye Va Boyer Ahmad stand in the first top places and three provinces of Tehran, Sistan-Baluchestan, and Kurdistan stand in the last places, respectively. 4- ConclusionRegarding urban employment indices, the cities of the country are from being developed and only 8 cities possess a semi-developed standing while other cities are in a state of underdevelopment. There is no considerable inequality and unevenness among cities in terms of urban employment development and also, cities with a higher ratio of population do not enjoy a higher level of urban employment development. Concerning the lowly developed conditions of some cities in comparison to other cities in regard with urban employment, in order to maintain and improve the equilibrium of the urban system of the country in the long run, it is recommended that any intervention in the urban employment of our cities be carried out based a well-informed prioritization.Keywords: employment indices, urban employment, spatial distribution, inequality, TOPSISReferencesAkhavan e saraf, Ahmadreza & Nilforooshzade, Maryam (2009), Factors defeat the implementation of continuous improvement based on AHP, Journal of Executive Management, Vol 9, No 1 (Summer), PP 13-36.Amini e Faskhudi, Abbas (2005), Application of Fuzzy Logic Inference in Studies of Regional Planning and Development, Journal of Knowledge and Development, No 17, pp 39-61.Bollinger, Christopher R & Ihlanfeldt, Keith R (2003); The intra urban spatial distribution of employment: which government interventions make a difference?, Journal of Urban Economics, Volume 53, Issue 3, May 2003, Pages 396-412Dadfar, Aram (2002), A Study of Quantitative Employment Changes in Different Economic Sectors by the use ofInput-output Tables in the Economy of Iran (1969-96), M.A. Thesis, Supervisor: Piraste, Hossein, Adviser: Banouei, Ali asghar, Isfahan University, Faculty of Administrative Science and Economic,Department o Economic Science.Farhoudi, Rahmatollah, Zanganeshahraki, Saeed & Saedmocheshi, Ramin (2009), Quality of spatial distribution of population in urban systems during the years 1335 to 1385, Human geography researches Quarterly, No 68 (summer), pp 55-68.Gharakhloo, Mehde & Zanganeshahraki, Saeed (2009), Recognition of Physical - Space growth pattern the city using quantitative models (Case Study: City of Tehran), Journal of Geography and Environmental Planning, Vol 20, No 2 (Summer), PP 19-40.Hajipoor, Khalil & Zebardast, Esfandyar (2005), Investigate, analyze and provide a model for urban systems Khuzestan, Journal of Fine Arts, No 23 (fall), pp 5-14.Hatamizade, Zivar & Mirshamsi, Arash (2004), Determine the effect of fiscal policy (taxes and spending) on the Iran's level of employment, Research and policies economic, No 31 (Fall), pp 3-28.Hekmatnia, Hasan & Mousavi, Mirnajaf (2006), model application in geography with emphasis on urban and reginal planning, Yazd, Elme Novin Publications.Hosseini, Sayed Mahmood, Safari, Hossein, Hosseini, Farshid, Ebrahimi, Abbas & Jamali, Ali (2008), Investigation and analyze the results of privatization in companies vested with banks and mining industry performance measurement approach, Journal of Commerce Quarterly, Vol 48 (Fall), pp 231-267.http://www.sci.org.irIzadi, Bahram (1009), Suppliers Selection Using Fuzzy AHP and TOPSIS (Case Study: SaIran Electro-Optic Industries Co), M.A. Thesis, Supervisor: Ketabi, Saeed, Adviser: Shahin, Arash, Isfahan University, Faculty of Administrative Science and Economic, Department o Management.Kohansal, Mohamadreza & Rafiei, Hadi (2008), Selection and ranking of traditional And irrigation systems in Khorasan Razavi province, journal of Agricultural Sciences and Industries, Special Of agricultural economic and development, Vol 22, No 1, pp 91-104.Kou, Ying & Xiong, Jiangen (2009); Entropy-based Improved TOPSIS as a Measure of Selecting Partner in Strategic Alliance, International Journal of Business and Management Economy, Volume 1, Issue, No.6.Massoumi Eshkevari, Seyed Hasan (2004), Industrial development and regional disparites in Iran (1960s onward), PH.D Thesis, Supervisor: Zebardast, Esfandiar, Adviser: Saeednia, Ahmad, Tehran University, faculty of fine, Arts, Department of Urban and Regional Planning.Mesriyenejad, Shirin & Torki, Leila (2004), Analyzing the structure of employment in major economic sectors of urban areas during the period 1983-2003, Journal of Social and Human Sciences, Vol 4, No 15 (Winter), pp 109-128.Meyanabadi, Hojat & Afshar, Abbas (2008), multiple indexes Decision in Ranking projects of urban water supply, Journal of Water and Wastewater, No 66 (Summer), pp 34-45.Mirfakhroldini, sayed Heidar, Farid, Darush & Sayaditouranloo, Hossein (2009), using EFQM models in analysis of dimensions of organizational culture in health care centers (Case Study: hospitals of Yazd), Journal of Medical Sciences and Health Services - Health Shahid Sadoughi University of Yazd, Vol 17, No 2 (Spring), pp 30-42.Mirghafouri, Sayed Habibollah, Sayaditouranloo, Hossein & Fahimi hanzaei, Saeede (2007), Identify and rank the affecting barriers on women's entrepreneurial activities using MCDM techniques (Case Study: Women entrepreneurs of Yazd province), journal of women, Vol 1, No 2 (Fall), pp 32-60.Mohamadi deh chashme, Pejman (2007), Space - Spatial Analysis of economic structure of employment in the province of Chahar Mahal and Bakhtiari by spatial ratio method, Geography Education Growth, Vol 21, No 4 (Summer), pp 43-50.Mohamadzade titkanloo, Hamide (2002), Capacity building in the cities of medium and regional spatial development, Case Study: City of Bojnourd and Khorasan Province, Journal of Fine Arts, No 12 (Winter), pp 33-49.Momeni, Mansour & Jahanbazi, Afshin (2007), designs a fuzzy multiple indexes Decision Model for selecting managers, Daneshvare Raftar, No 26, pp 1-16.Momeni, Mehdi (2008), Principles and methods for regional planning, Najaf Abad, Islamic Azad University of Najaf Abad Publications. Morsali, Edris (2006), Investigation of inequalities urban-rural employment of West Azarbaijan Province during 1962-2006 years, Rural and Development Quarterly, No 2 (Summer), pp 77-103.Önüt, Semih & Soner, Selin (2008); Transshipment site selection using the AHP and TOPSIS approaches under fuzzy environment, Waste Management, Volume 28, Issue 9, Pages 1552-1559Ostadhossein, Reza (2004), Investigation of Factors Affecting the country's industrial employment, research of economic and political Quarterly, No 30 (summer), PP 93-126.Panahi, Rajab & Morsali, Edris (2006), Investigation of Inequalities urban-rural employment of country during 1962-2006 years, Journal of agricultural economics and development, Vol 14, No 56 (Winter), pp 143-166.Pourahmad, Ahmad (2001), Land preparation and balancing the country's urban system, journal of Faculty of Literature and Humanities Tehran University, No 160 (Winter), pp 167-180.Saeedneya, Ahmad (2004), Green Book Municipality, Volume 11, Urban Management, Tehran, shahrdariha and Dehyariha Publications.Saraf, Hasan & Najmi, Mohamadreza (2004), Introduction a methodical model to evaluate options determine the items quality, the first national conference logistics and supply chain, Tehran, Iran Logistics Society.Sayareh, Morteza (2009), Analysis of Regional Employment Disparities and Ranking Provinces Based on Decent Work, M.A Thesis, supervisor: Bakhtiari, Sadegh, Adviser: Sasan, Abdolhossein, University, Faculty of Administrative Science and Economic, Department o Economic Science.Shafieiroudposhti, Meysam & Mirghafouri, Sayed Habibollah (2008), Identify and ranking Effective factors on quality improvement of educational services of higher education (Case Study: management College of Yazd University), Journal of higher education of iran., No 2 (Fall), pp 67-93.Shakoei, Hossein (2006), the New Opinions in Urban Geography (Volume 11), Tehran, Samt Publication. Tabatabayi e Yazdi, Roya (2006), parameter and indicators Futurists and simultaneous of employment, Strategy Quarterly, No 40 (summer), PP 215-224.Taherkhani, Mehdi (2000), Analytical effective factors in rural migration to urban, new orientations and discussions, rural and development Quarterly, Vol 4, No 3-4 (Fall and Winter), pp 1-24.Taherkhani, Mehdi (2007), usage TOPSIS technique in establishing spatial priorities agricultural conversion industries in rural areas, Economic Research Quarterly, Vol 6, No 3 (Fall), pp 59-73.Tarahomi, Farhad (2007), Recognize key parts of the economy from the viewpoint of employment, Economic journal, No 73 & 74, pp 65-86.Tavari, Mojtaba, Sukhkian, Mohamadali ana Mirnejad, Sayed Ali (2008), Identify and prioritize the factors affecting of human resources productivity using MADM techniques (Case Study: One of Jin garment companies in Yazd province), Journal Industrial Management, Vol 1, No 1 (Fall and Winter), pp 71-88.United Nations (2005); Human Development Report 2005, Published for the United Nations Development Program (UNDP), New York.Valibeigi, Hasan (2006), Prioritizing of target markets of exportable and barriers in their presence (Case Study: Selection of export food products), Journal of Commerce Quarterly, No 41 (winter), pp 53-89.Wang, Yu-Jie & Lee, Hsuan-Shih (2007); Generalizing TOPSIS for fuzzy multiple-criteria group decision-making, Computers and Mathematics with Applications, Volume 53, Issue 11, June 2007, Pages 1762-1772Yahyaabadi, Abolfazl (2002), Theoretical and empirical analysis of the structural changes and its impact on employment in Iran, PH.D Thesis, Supervisor: Bakhtiari, Sadegh, Adviser: Dallali esfahani, Rahim & Sameti, Morteza, , Isfahan University, Faculty of Administrative Science and Economic, Department o Economic Science.Yasouri, Majid (2005), Regional Policy making and quality inequalities in the country, Journal of political- economy, No 7 & 8, pp 138-145.Zangiabadi, Ali (200), The Analysis & Spatial Construction Organizing of Urban development Indicators in + 100000 Cities of Iran, PH.D Thesis, Supervisor: Talebi, Hooshang & Hedayat, Mahmmod, Adviser: Shafaghi, Sirus, University, Faculty of Literature and Human Sciences, Department o Geography, Branch, Urban Planning.Zarabi, Asghar & Mousavi, Mirnajaf (2009), A survey on function of fmall cities in the urban system and regional development (Case study: Yazd Province), Journal of Geography and Environmental Planning, Vol 20, No 2 (summer), PP 1-18.